THE ASSOCIATION «COMMONWEALTH OF EDUCATIONAL ORGANIZATIONS NAMED AFTER A.S. PUSHKIN AND TEACHERS» AS A RESPONSE TO THE SOCIOCULTURAL TRANSFORMATION IN EDUCATION (Uzbekistan Open Conference, 2025)
The article examines the example of the activities of the international Association «Commonwealth of Educational Organizations named after A.S. Pushkin and Teachers» as a practical model of response to the crisis of identity of traditional educational institutions. The study focuses on the concept of a methodological system for developing a spiritual and moral personality in the modern educational paradigm of Pushkin’s Pedagogy as a value-based and activity-oriented system that allows for the preservation of the cultural code and ensures a dialogue of cultures in the context of globalization.